Evaluation of outcome of chemotherapy for breast cancer patients older than 70 years: A SEER-based study - Pu, Shengyu; Xie, Peiling; Chen, Heyan; Li, Yijun; He, Jianjun; Zhang, Huimin (Frontiers in Oncology, 2023)
Background: With the aging of the population, the number of elderly breast cancer cases has increased. However, there is a lack of effective randomized clinical trial data to support whether elderly patients should receive chemotherapy. Our goal was to observe the relationship between chemotherapy and breast cancer-specific survival (BCSS) in elderly breast cancer patients and to identify those who could benefit from chemotherapy. Methods: We collected the data of patients who were diagnosed with invasive ductal carcinoma and older than 70 years in the SEER database from 1995 to 2016. The independent predictors of BCSS were identified by Cox regression analysis. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) were performed to eliminate confounding factors. Results: A total of 142,537 patients were collected, including 21,782 patients in the chemotherapy group and 120,755 patients in the non-chemotherapy group. We identified the same potential predictors of BCSS after PSM and IPTW, such as age, race, grade, stage, therapy, subtype. A nomogram for predicting 3-year, 5-year and 10-year BCSS was constructed. The 3-year, 5-year and 10-year AUCs of the nomogram were 0.842, 0.819, and 0.788. According to the risk stratification of model predictive scores, patients in the high-risk group achieved the greatest improvement in BCSS after receiving chemotherapy. Conclusions: Our study suggests that women older than 70 years with larger tumors, higher grade, positive nodes, negative hormone receptor and inactive local therapy gain prognostic benefits from chemotherapy, but for those with low- and median-risk, conventional chemotherapy should be administered cautiously.